Informed Consent as Compelled Professional Speech: Fictions, Facts, and Open Questions - Nadia N. Sawicki (Washington University Journal of Law & Policy, 2016)
This article explores the relationship between a physician’s First Amendment right to free speech and state informed consent mandates. Sawicki details the convoluted jurisprudence surrounding consent mandates, focusing on one-sided and controversial subject matter that many states require physicians to disclose. Sawicki then offers a legal framework for how a physician-challenged consent mandate may pass through the court system based on existing Supreme Court jurisprudence.
Keywords: First Amendment; Physician speech; Healthcare; Professional speech; Regulation; Informed consent